Perception level among clinical officers’ students on the effectiveness of simulation models in the Department of Clinical Medicine - B. K. Wamalwa (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction Clinical simulation learning as an educational tool is recommended in the clinical officers’ training. Upon entry into the workforce, clinicians are expected to respond to a range of clinical situations they may not have experienced during their program.Methodology. A cross-sectional survey was conducted at Two medical training colleges in Kakamega County, Kenya. This design also enabled testing of causeand-effect relationships of the variables under study. The study employed a systematic way of gathering information. The information gathered described simulation in clinical teaching, specifically a case study of medical training colleges in Kakamega County Kenya.Results. The results show that 215 (71.2%) of the respondents agreed that assessment in the skills laboratory improved the outcome of the early clerkship, 77 (25.5%) disagreed while 10 (3.3%) of the respondents were neutral. The mean score was 3.14 with a standard deviation of 1.14 which shows that most respondents were in agreement that assessment in skills laboratory improves the outcome of the performance and skills of students. The item mean was below the composite mean of 3.36 indicating a negative influence on the composite mean. The standard deviation for the item was above the composite standard deviation of 0.45 indicating a wider spread in response for the item than the variable.Conclusion. OSCE is a competency-based tool widely used in clinical teaching.